2022
DOI: 10.1101/2022.08.29.505663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The claudin-like apicomplexan microneme protein is required for gliding motility and infectivity of Plasmodium sporozoites

Abstract: Invasion of host cells by apicomplexan parasites such as Toxoplasma and Plasmodium spp requires the sequential secretion of the parasite apical organelles, the micronemes and the rhoptries. The claudin-like apicomplexan microneme protein (CLAMP) is a conserved protein that plays an essential role during invasion in Toxoplasma gondii tachyzoites and Plasmodium falciparum merozoites. CLAMP is also expressed in Plasmodium sporozoites, the mosquito-transmitted forms of the malaria parasite, but its role in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Investigating the three mutants we found that all formed similar numbers of sporozoites in oocysts and that all could colonize the salivary glands to similar levels (Figure 2C). Sporozoites move at high speeds and thus deletion of genes often affects their gliding motility (43,(46)(47)(48). To investigate gliding activity, we allowed salivary gland derived sporozoites to settle on a glass substrate and imaged their movement.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating the three mutants we found that all formed similar numbers of sporozoites in oocysts and that all could colonize the salivary glands to similar levels (Figure 2C). Sporozoites move at high speeds and thus deletion of genes often affects their gliding motility (43,(46)(47)(48). To investigate gliding activity, we allowed salivary gland derived sporozoites to settle on a glass substrate and imaged their movement.…”
Section: Resultsmentioning
confidence: 99%
“…The latter corroborates prior work, which found that inhibitory antibodies to Pf SPATR can block P. falciparum invasion of blood cells (Chattopadhyay et al , 2003). In P. berghei , Pb SPATR is required for blood stages and sporozoites, suggesting the CLAMP complex is important for host cell invasion in multiple stages of the parasitic life cycle (Gupta et al , 2020; preprint: Costa et al , 2022; Loubens et al , 2023). Though we were unable to generate a conditional knockdown strain for Pf CLIP, the PlasmoGEM project finds that the CLIP homolog in P. berghei is also essential during blood stages (Bushell et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both scenarios are possible because the details of this complex are not known. Similar to S14, several parasite proteins play a role in the gliding motility and invasion of both mosquito and human hosts, such as surface protein TRAP (Sultan et al, 1997) and claudin-like apicomplexan microneme protein (CLAMP) (Loubens et al, 2023); however, MAEBL was found to be important for attachment to the salivary gland surface and did not affect sporozoite motility and infectivity to the vertebrate host (Kariu et al, 2002). S14 is not a surface protein with an extracellular domain, and its host cell invasion defect was due to impaired gliding.…”
Section: Discussionmentioning
confidence: 99%
“…S6 is also a TRAP family adhesion, and by disruption, its role has been implicated in parasite adhesion and gliding motility (Steinbuechel & Matuschewski, 2009). The other proteins involved in parasite motility and host cell invasion include MAEBL (Kariu et al, 2002;Saenz et al, 2008), TLP (Heiss et al, 2008), the rhoptry-resident proteins TRSP (Labaied et al, 2007), RON4 (Giovannini et al, 2011), GEST (Talman et al, 2011), TREP/UOS3 (Mikolajczak et al, 2008;Combe et al, 2009), the GPI-anchored circumsporozoite protein (CSP) of the sporozoite and the small solute transporter PAT (Kehrer et al, 2016) and claudin-like apicomplexan microneme protein (CLAMP) (Loubens et al, 2023). The individual functions of these proteins are known.…”
Section: Introductionmentioning
confidence: 99%